Análise evolutiva, metabólica e pangenômica de Ralstonia solanacearum - Juan Carlos Ariute Oliveira (2022)
Strains of Ralstonia solanacearum species complex (RSSC) cause several phytobacteriosis in many economically important crops worldwide, especially in the tropics. In Brazil, phylotypes I and II are causal agents of bacterial wilt, preventing their distinction. In turn, Moko disease is caused only by phylotype II strains. Analyses with the genomes of RSSC strains suggested that many virulence factors and secretion systems were involved in successful pathogenicity. Subsequently, studies focused on the suite of secreted molecules of R. solanacearum revealed an extremely diverse secretome composed mostly of type III effectors (T3Es), or Ralstonia injected proteins (Rips). The secretome plays essential roles in bacterial recognition, subversion of host defense mechanisms, metabolic modulation, cell wall degradation, host specificity, and other yet unknown functions. In this work, we sequenced and characterized 14 new RSSC isolates from northern and northeastern regions of Brazil belonging to bacterial wilt (BW) and Moko ecotypes. The virulence and resistance mechanisms were annotated and the Rips repertoire was predicted for each isolate. Corroborating with past studies, the RSCC pangenome is open, as α ≅ 0.77. The genomic information of expected size and amount of coding sequences (CDSs) also corroborates with those described for R. solanacearum at NCBI. All the 14 new genomes sequenced cluster in phylotype II with similarity above 96%, with five isolates in phylotype IIB and nine in phylotype IIA. Furthermore, almost all genomes classified as R. solanacearum in NCBI actually belong to other species of the complex. In total, 43 Rips were shared between all 14 isolates. The Rips repertoire of the Moko IIB isolates was more homogeneous, except for isolate B4, which had 10 Rips not shared among the other four isolates. The Rips repertoire of the IIA isolates was more diverse in both BW and Moko isolates. Interestingly, the new BW isolates shared more Rips with Moko IIA and Moko IIB isolates than with other public genomes of Brazilian BW isolates. Rips that were not shared among all isolates may contribute to individual virulence, while commonly shared Rips may be good candidates for avirulence. The high number of shared Rips among the new isolates of Moko and BW suggests that these isolates may be capable of infecting the Solanaceae plants. Functional enrichment analyses of the genomes of the 14 isolates revealed the presence of genes for structural proteins of the type III secretion system and hrc/hrp genes and AraC regulators, however, failed to identify most of the effectors predicted for the repertoire. The protein-protein interaction with Rips, T3SS structural genes, and transcriptional regulators analysis was able to identify 70 of 89 candidates in the B4 genome, 203 interactions and an average degree of 6.03 per node. The delimitation of specific gene repertoires of each phylotype in the complex via pangenomic analyses offers potential targets for diagnostic kits to detect isolates of the respective complexes. Finally, infection and Rip gene expression assays in different hosts are needed to better elucidate the association between the effector repertoire and host specificity, to aid in the understanding of gene regulation during pathogenesis.